Richard Stanford papers - Stanford, Richard, 1767-1816.
Two ALS (1804 February 6 and 1808 February 27) written by Stanford to his wife, Mary Moore Stanford; typewritten transcript and printed copy of a letter (1803 February 26) written by Stanford to James Patterson relating to national politics and comparing the presidential administrations of John Adams and Thomas Jefferson; typescript biographical sketch (undated) of Stanford by Samuel Lee Adams; and lithograph portrait of Stanford.
In part, typewritten transcripts.
U.S. representative from North Carolina.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Adams, John, -- 1735-1826.; Adams, Samuel Lee; Jefferson, Thomas, -- 1743-1826.; Patterson, James, -- active 1803 -- Correspondence; Stanford, Mary Moore, -- active 1796-1808.; United States -- Politics and government -- 1797-1801.; United States -- Politics and government -- 1801-1809.; Representatives, U.S. Congress -- North Carolina